2016
DOI: 10.5507/bp.2016.019
|View full text |Cite
|
Sign up to set email alerts
|

Omentin-1 levels in patients with premature coronary artery disease, metabolic syndrome and healthy controls. Short communication

Abstract: Objectives. Omentin-1 is an adipokine which could have a protective role against the manifestation of atherosclerosis. Only limited data are available on omentin-1 serum values in patients with premature clinical manifestations of atherosclerosis.Design and Methods. We tested omentin-1 in human serum by ELISA method in 61 individuals with a premature manifestation of coronary artery disease (CAD), 40 patients with metabolic syndrome and 40 healthy control subjects. Results. Omentin-1 serum levels were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…To our knowledge, our group is the first to assess omentin-1 levels in "young" patients with premature manifestations of atherosclerosis [11]. The results are in accordance with studies in older patients.…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, our group is the first to assess omentin-1 levels in "young" patients with premature manifestations of atherosclerosis [11]. The results are in accordance with studies in older patients.…”
Section: Discussionsupporting
confidence: 89%
“… 4 Inflammation is caused by several hormones like proteins called adipokines, released from adipose tissues, which now, considered as main endocrine tissue of the body. 5 Omentin-1 is a recently identified, visceral adipose tissue derived adipokine consists of 295 amino acids, coded by gene located at chromosome 1q 21-23. 6 , 7 Omentin-1 is reported to be highly expressed in epicardial adipose tissue (EAT) around the heart and coronary arteries.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial calcification is positively associated with visceral adiposity, but the mechanisms remain unclear. Several experimental studies demonstrated the protective role of omentin-1 in the regulation of atherogenesis [182]. This study demonstrated that recombinant human omentin-1 could induce OPG and inhibit RANKL production in primary mouse osteoblasts and calcifying vascular smooth muscle cells (CVSMs) in vitro, and adenovirus-mediated over-expression of human omentin-1 in OPG -/mice could ameliorate bone loss and arterial calcification in vivo.…”
Section: Omentin-1 Attenuates Arterial Calcification and Bone Lossmentioning
confidence: 74%